(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2025)
The film A Fantastic Woman depicts three days in the life of a transgender woman who has just lost her male partner. Throughout its development, the film unfolds as a dialectic between urban scenes shaped by the selection and cinematic treatment of its locations and the protagonist’s transformations and struggles. The purpose of this research, undertaken through a descriptive film analysis and a correlational study of the locations, is to identify and describe these relationships between space and the subject’s transformations. Over the course of the film, the character achieves a profound consolidation of her identity, within a spatial organization described as a succession of transitions and thresholds, highlighting how the latter, as moments of intense transformation, occur mainly in underground spaces. Through this spatial construction, which moves away from the conventional tropes of the filmed city, the fusion of representations and locations becomes evident in narrating Marina’s evolution toward a more universal identity—one that transcends the heterosexual matrix, opposes glamorous visions of transsexual, and embraces behaviors spanning multiple genders and even species. This exercise unfolds in a dual relationship with spatiality: first, in the handling of locations and the topological construction to be described; and second, in how the filmic choices produce a highly empathetic perception of the protagonist and her experience of space.